Optimal common limb length in Roux‐en‐Y gastric bypass surgery: is it important for an ideal outcome? – a systematic review. Issue 4 (8th December 2022) - Hort, Amy; Cheng, Qiuye; Morosin, Tia; Yoon, Peter; Talbot, Michael
Abstract: Background: In Roux‐en‐Y gastric bypass (RYGB) surgery the common limb length (CLL) is thought to significantly impact on nutritional and metabolic outcomes. However, there has been little focus on establishing routine standardized CLL measurements and its subsequent effect on weight loss and nutritional status. This review aimed to determine the effect of variations of CLL in RYGB surgery on post‐operative outcomes, particularly nutritional status, while considering the need for routine CLL measurements in addition to measuring biliopancreatic limb and alimentary limb lengths. Methods: A systematic review was performed in accordance with the PRISMA guidelines. All English language articles addressing CLL and impact on weight loss, nutritional and metabolic outcomes were retrieved and reviewed. Results: Thirteen relevant studies were identified with CLLs varying from 76 to >600 cm. No significant difference in total body weight loss or excess weight loss was observed. Significant metabolic improvements occurred with shorter CLLs. Nutritional deficiencies were more severe when the CLL was <400 cm. Conclusion: The data from this systematic review suggests that reasonable weight loss and positive impacts on metabolic outcomes can be achieved with CLLs of >400 cm. Abstract : The common limb length in Roux‐en‐Y gastric bypass surgery has the potential to impact nutritional and metabolic outcomes, with this review study demonstrating reasonable weight loss and positive impacts on metabolic outcomes with common limb lengths >400 cm.